The unhealthy divide: how the secular-faith binary potentially limits GBV prevention and response. Issue 5 (4th July 2017) - le Roux, Elisabet; Loots, Lizle
ABSTRACT: While progress has been made in creating conversations between the secular and faith actors involved in developmental issues, a distinct binary still exists. This could potentially be limiting a holistic response to gender-based violence, a global public health, development, humanitarian, and human rights issue. This article explores how perceptions of this binary – faith versus secular – are understood to impact GBV prevention and response efforts. Drawing on interviews conducted during a scoping study, the opinions and experiences of actors from faith-based organisations and academic institutions are used to shed light on how the faith-secular binary is being upheld and challenged, and how it is perceived to be impacting holistic GBV prevention and response.